Building brand relationship for restaurants: An examination of other customers, brand image, trust, and restaurant attributes. Issue 3 (12th February 2019) - Erkmen, Ezgi; Hancer, Murat
Abstract : Purpose: The purpose of this study is to examine the role of other customers in explaining customers' relation with a brand. A conceptual model, which incorporates other customers along with atmospherics, food quality and service quality, is proposed to better understand how customers form their brand preference for fine dining restaurants. Design/methodology/approach: A quantitative research methodology, using structural equation modeling, was adopted to understand the role of other customers along with other restaurant attributes. Data were collected from the customers of fine dining restaurants resulting in 324 usable surveys. Findings: The findings supported the sequential link for: restaurant experience attributes – brand relationship and brand preference. While all restaurant attributes except other customers explain the satisfaction of customers, only service quality and other customers played a significant role in forming the brand image in the minds of restaurant guests. Overall, this study acknowledged the importance of both other customers and employees in fine dining restaurants' branding. Research limitations/implications: The results suggest that customers in servicescape have a significant role in creating a successful brand image for restaurants. Moreover, service quality is also key to achieve a unique image, thereby suggesting that employees could be a source of differentiation and competitive advantage by managing their brand related behaviors. Originality/value: This research was one of the first to study the role of other customers in restaurant service experience along with other attributes to assess customers' brand relation and brand preference for fine dining restaurants.